Indicator for Brake Lights (INBREL) / Mohd Azam Che Seman ... [et al.] - Che Seman, Mohd Azam; Ghini, Mohd Sufian; Mohd Nor, Mohd Sabri; Che Sukri, Che Mohd Saiful Azhar; Hamzah, Najmuddin (2024)
The detection of failures in vehicle lighting systems is crucial for enhancing vehicle safety and quality. Malfunctioning brake and tail lights can pose significant safety risks, as drivers may be unaware of these failures and consequently face higher chances of being involved in accidents. This project aims to address this critical issue by developing an innovative system that provides a warning signal to drivers in the event of brake or tail light failure. The proposed system, named the Indicator for Brake Lights (InBreL), includes an advanced control module that continuously monitors the functionality of the vehicle's brake and tail lights. Upon detecting a malfunction, the InBreL Control Module (ICM) promptly alerts the driver, enabling them to take immediate corrective action. This proactive approach not only enhances vehicle safety by preventing potential accidents but also provides car owners with an additional safety feature that ensures they are always aware of the operational status of their vehicle's lighting system. Throughout the project, various testing and validation processes were conducted to ensure the reliability and effectiveness of the ICM. The final product, the InBreL Control Module, demonstrated high reliability and ease of integration into existing vehicle systems, making it a practical solution for improving road safety, with its core component designed to notify drivers of any issues with the brake light system.